Preliminary In Vivo Experiments on Adhesion of Geckos. (22nd May 2008) - Lepore, E.; Brianza, S.; Antoniolli, F.; Buono, M.; Carpinteri, A.; Pugno, N.
Abstract : We performed preliminary experiments on the adhesion of a Tokay gecko on surfaces with different roughness, with or without particles with significant different granulometry, before/after or during the moult. The results were analyzed using the Weibull statistics.